PERFORMANCE AESTHETICS IN ENVIRONMENTAL GRAPHIC DESIGN AND ITS VISUAL IMPACT - Dalia Salem Mohamed Abdul Latif (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
Recreating our design vision in everything that surrounds us in this world, of which we are an integral part, is the basis that will determine the standards that will be measured against achieving sustainable creativity, through us humans and how we adapt to the planet, especially the ability of the designer who can through the positivity of his designs to change the world.We must know that the artistic process is a process of development and expansion of visual or verbal design, which results in a specific vision. And the artist’s relationship with his artistic medium is always one of renewal and inspiration, not one of conflict and tension. The material is not a limitation or a challenge over the long term, but data, stock and inspiration as well. Therefore, we find that modern technologies may provide the artist with different media that do not exist in nature, giving him plastic capabilities that he does not entrust and open up He has unconventional ways to bring his artwork to a new expressive value.We often see that the material is what inspires the artist and the designer, takes his hand and guides him. This means that the common element among all works of art is the style and method of organizing these materials with the artistic sense that provokes us with aesthetic emotion. Movement, and these elements cannot be separated from each other in the way they are formed,